Targeting to high density lipoprotein cholesterol: new insights for inflammatory bowel disease treatment - Xiaotong Wang; Xuefei Li; Kezhen Liu; Ke Yi; Yang Yang; Dongwen Wu; Xiaowei Liu (Journal of Lipid Research)
The anti-inflammatory and vasoprotective properties of HDL-C make it best known in cardiovascular disease and sepsis. We aimed to investigate whether interventions that target HDL-C metabolism may be used for the prevention and treatment of inflammatory bowel disease (IBD). The relationship between serum lipids and IBD clinical manifestations were analyzed in both respective and prospective cohort. Later, therapeutic effect and mechanism of cholesteryl ester transfer protein inhibitors (CETPis) in IBD treatment were explored by in vivo experiments. IBD patients had significantly reduced HDL-C, which was negatively correlated with their inflammatory status. Furthermore, HDL-C level was elevated by biologics agents and HDL-C concentration pretreatment was predictive for IBD patients’ future disease severity. Elevating HDL-C by CETPi before or even after the onset of experimental colitis reduced disease severity, which is associated with an ATF3-dependent anti-inflammatory reprogramming of macrophages and with enhanced gut barrier function. Together, these results demonstrate an important role of HDL-C in IBD and indicate the potential pharmacological effects of CETPi for future IBD therapy through elevation of HDL-C.